Novel Approaches to Profile Functional Long Noncoding RNAs Associated with Stem Cell Pluripotency - Zhu, Yanbo; Yan, Zi; Tang, Ze; Li, Wei (Current Genomics, 2020)
The pluripotent state of stem cells depends on the complicated network orchestrated by thousands of factors and genes. Long noncoding RNAs (lncRNAs) are a class of RNA longer than 200 nt without a protein-coding function. Single-cell sequencing studies have identified hundreds of lncRNAs with dynamic changes in somatic cell reprogramming. Accumulating evidence suggests that they participate in the initiation of reprogramming, maintenance of pluripotency, and developmental processes by cis and/or trans mechanisms. In particular, they may interact with proteins, RNAs, and chromatin modifier complexes to form an intricate pluripotency-associated network. In this review, we focus on recent progress in approaches to profiling functional lncRNAs in somatic cell reprogramming and cell differentiation.
Keywords: stem cells